Microdiffraction analysis of structure of silumin's high-velocity cellular crystallization; Journal of Physics: Conference Series; Vol. 1393 : Gas Discharge Plasmas and Their Applications (GDP 2019) - Petrikova E. A. Elizaveta Alekseevna; Teresov A. D. Anton Dmitrievich; Rygina M. E. Mariya Evgenjevna; Tolkachev O. S. Oleg Sergeevich; Ivanov Yu. F. Yuriy Fedorovich; Gromov V. E.; Zagulyaev D. V. Dmitry Valerjevich; Konovalov S. V.; Semin Aleksandr Petrovich A. P. Aleksandr Petrovich (2019, 2019)
Title screen